2020
DOI: 10.33546/bnj.971
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Care Intervention on Oral Health Status of Intubated Patients in the Intensive Care Unit

Abstract: Background: Oral infections can be a potential source of infection resulting in a variety of systemic diseases, especially in intubated patients in an Intensive Care Unit (ICU). Endotracheal tube (ETT) of the intubated patient’s mouth can be an entry point and place of bacteria colonization that causes ventilator-associated pneumonia which is one of the causes of the patient’s death in ICU. Nurses as caregivers have an important role in providing oral care intervention to maintain oral health and prevent the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
2
13
1
1
Order By: Relevance
“…In their study, Kaya et al (26) showed that the use of chlorhexidine mouthwash alone improved oral health. Inconsistent with the present study's results, Anggraen et al (27) showed that the oral care program had a deteriorating effect on oral health in intubated patients during the study period. Also, the results of Prendergast's study (28) are inconsistent with the present study's results.…”
Section: Discussionsupporting
confidence: 59%
“…In their study, Kaya et al (26) showed that the use of chlorhexidine mouthwash alone improved oral health. Inconsistent with the present study's results, Anggraen et al (27) showed that the oral care program had a deteriorating effect on oral health in intubated patients during the study period. Also, the results of Prendergast's study (28) are inconsistent with the present study's results.…”
Section: Discussionsupporting
confidence: 59%
“…Patients in critical care and nervous system disorders tend to experience impaired oral hygiene. Oral cavity infections can be a potential source of infection that can lead to various systemic diseases, especially in patients with an endotracheal tube (ETT) in the Intensive Care Unit (ICU) (Anggraeni, Hayati, & Nur'aeni, 2020). The ETT in the mouth of an intubated patient can be the entrance and site for bacterial colonization that causes Ventilator Associated Pneumonia (VAP) which is one of the causes of patient death in the ICU (Cooper, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses as caregivers have an important role in providing oral care interventions to maintain oral health and prevent infection (Anggraeni et al, 2020). On the other hand, the level of knowledge of nurses and doctors regarding oral care to prevent bacterial colonization in the oral cavity and oropharynx is still low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the entry of bacteria into the respiratory tract can be caused by intraoral plaques and biofilm layers, increasing the risk of infection. [3][4][5][6] Inadequate oral hygiene increases the risk of mortality by causing fatal complications such as ventilator-associated pneumonia (VAP). [1][2][3][4][5] Oral care is a basic nursing care application in the ICU, and evidence-based application guidelines have been established.…”
Section: Introductionmentioning
confidence: 99%